Diagnosis of Fibromyalgia: Disagreement Between Fibromyalgia Criteria and Clinician‐Based Fibromyalgia Diagnosis in a University Clinic. Issue 3 (6th February 2019) - Wolfe, Frederick; Schmukler, Juan; Jamal, Shakeel; Castrejon, Isabel; Gibson, Kathryn A.; Srinivasan, Sachin; Häuser, Winfried; Pincus, Theodore
Abstract : Objective: Recent studies have suggested that fibromyalgia is inaccurately diagnosed in the community, and that 75% of persons reporting a physician diagnosis of fibromyalgia would not satisfy published criteria. To investigate possible diagnostic misclassification, we compared expert physician diagnosis with published criteria. Methods: In a university rheumatology clinic, 497 patients completed the Multidimensional Health Assessment Questionnaire (MD‐HAQ) and the 2010 American College of Rheumatology preliminary diagnostic criteria modified for self‐administration during their ordinary medical visits. Patients were evaluated and diagnosed by university rheumatology staff. Results: Of the 497 patients, 121 (24.3%) satisfied the fibromyalgia criteria, while 104 (20.9%) received a clinician International Classification of Diseases (ICD) diagnosis of fibromyalgia. The agreement between clinicians and criteria was 79.2%. However, agreement beyond chance was only fair (κ = 0.41). Physicians failed to identify 60 criteria‐positive patients (49.6%) and incorrectly identified 43 criteria‐negative patients (11.4%). In a subset of 88 patients with rheumatoid arthritis (RA), the kappa value was 0.32, indicating slight to fair agreement. Universally, higher polysymptomatic distress scores and criteria‐based diagnosis were associated with more abnormal MD‐HAQ clinical scores. Women and patients with more symptoms but fewer pain areas were more likely to receive a clinician's diagnosis than to satisfy fibromyalgia criteria. Conclusion: There is considerable disagreement between ICD clinical diagnosis and criteria‐based diagnosis of fibromyalgia, calling into question ICD‐based studies. Fibromyalgia criteria were easy to use, but problems regarding clinician bias, meaning of a fibromyalgia diagnosis, and the validity of physician diagnosis were substantial.